P0554IN VITRO ASSESSMENT OF HA330 CARTRIDGE ADSORPTION CAPACITY REALTED TO VANCOMYCIN. (6th June 2020) - Lorenzin, Anna; Godi, Llaria; De Cal, Massimo; Ronco, Claudio
Abstract: Background and Aims: The rationale for blood purification as adjunctive therapy during sepsis involved the capacity in removing endogenous and exogenous toxins, but currently no recommendations exists [1]. A critical point may be the potential interaction with antimicrobial therapy, which remains the mainstay of sepsis treatment. HA330 cartridge (Jafron, Zhuhai City, China), widely used in China and actually available in Europe, is used in hemoperfusion for blood purification in septic patients.The aim of this in vitro study was to investigate the adsorptive capacity of HA330 related to vancomycin (VAN). Reference: 1. Rhodes A et al. Crit Care Med 45:486-552. 2017 Method: This is an experimental study, simulating an hemoperfusion treatment with HA330. We circulated (250 ml/min) in a closed loop 500 ml of normal saline solution enriched with VAN, stirred and maintained at 37°C. We spiked 100 mg of VAN every 15 minutes to increase the antibiotic load until reaching 1500 mg, the last injection was 500 mg to get a total amount of 2 g. Samples were collected from the inlet line at each VAN adjunct, after system stabilization. Measured VAN concentrations were used to get the adsorption isotherm: for each VAN load, the adsorbed amount of VAN was obtained by multiplying VAN reduction ratio and the quantity of VAN injected. Results: Figure 1 shows VAN adsorption isotherm obtained with HA330 cartridge. We observed that, at each injection, after 15 minutes VAN was almost entirely adsorbed by the cartridge, with an average reduction ratio of 0.96. Interestingly, this was confirmed even adding 500 mg at once. Even increasing the VAN load to 500 mg at once, the reduction ratio was maintained. Conclusion: In our study, simulating hemoperfusion using HA330, a rapid and clinically relevant removal of VAN has been shown. A significant amount of VAN (2g) was adsorbed without reaching membrane saturation nor reducing its adsorptive capacity. In a clinical setting, we recommend a therapeutic drug monitoring to optimize VAN levels during blood purification with HA330 and a VAN loading dose may be considered. Further in vivo studies are warranted to confirm these findings.